Marketing Research, Global Edition - Burns, Alvin C.; Veeck, Ann; Bush, Ronald F. (Pearson International Content, 2019)
For courses in global marketing. A conceptual approach and introduction to the field of marketing research Written with an emphasis on the practical application of marketing research methods, Marketing Research teaches the basic fundamental statistical techniques needed to analyse market data. The 9th Edition has been updated to offer the most current insights on forces shaping marketing research, including the widespread adoption of infographics, a pronounced shift toward mobile marketing research, and the impact of big data. Additionally, an updated and integrated case study throughout the text helps students relate the material to the real world -- and their future careers. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.